Reply to the Letter to the Editor Regarding Our Article (Paganelli et al., 2010) - Carrasco, Andres Eduardo (2011)
To the Editor: The letter to the editor sent by representatives of Monsanto, Syngenta, and Dow Chemicals (among others) to Chem. Res. Toxicol. regarding our paper (Paganelli et al., published July 23, 2010) and the tone used in their criticismabout other research papers studying glyphosate effects should come as no surprise considering the obvious conflicts of interest inherent in this work when the companies selling a product are also solely responsible for testing its safety. These multinational corporations handle virtually all of the seed and chemical products market in the world; therefore, it cannot be inferred that research performed or supported by such companies is completely objective. Their dismissal of our research and that of other researchers harkens back to the ongoing debate about bisphenol A, where no single industry funded study has ever found adverse consequences linked with BPA exposure, whereas 90% (n > 100) of nonindustry funded studies show significant adverse consequences of BPA exposure. Therefore, we contend that rather than pointing out shortcomings of our research, the letter illustrates the increasing difficulty in dialogues between those with a vested interest in product sales and independent researchers who wish simply to understand whether the said products are safe. It is worse yet when multinational corporations attempt to use their own flawed science to hide and defend environmental devastation suffered by less-developed countries in areas where their products are heavily used with only minimal governmental scrutiny.